'Breaking the glass': preserving social history in virtual environments. (1st January 2011) - Kuksa, Iryna; Tuck, Deborah
New media technologies play an important role in the evolution of our society. Traditional museums and heritage sites have evolved from the 'cabinets of curiosity' that focused mainly on the authority of the voice organising content, to the places that offer interactivity as a means to experience historical and cultural events of the past. They attempt to break down the division between visitors and historical artefacts, employing modern technologies that allow the audience to perceive a range of perspectives of the historical event. In this paper, we discuss virtual reconstruction and interactive storytelling techniques as a research methodology and educational and presentation practices for cultural heritage sites. We present the Narrating the Past project as a case study, in order to illustrate recent changes in the preservation of social history and guided tourist trails that aim to make the visitor's experience more than just an architectural walk through.